2009
DOI: 10.1007/s11557-009-0647-8
|View full text |Cite
|
Sign up to set email alerts
|

A review of research on Chinese Tuber species

Abstract: Truffles are abundant in some regions of China. Nevertheless, it was not until the 1980s that Tuber species were discovered by Chinese mycologists. In recent years, international truffle markets have shown an increasing interest in the import of Chinese Tuber. These truffles serve as a complement to European truffles due to their lower prices and their greater availability in a deficit market. However, Chinese truffles have been the subject of fraudulent commercial practices, and these could have a negative ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 27 publications
0
17
1
1
Order By: Relevance
“…In this regard, it has been observed that Pinus nigra subsp. salzmannii produces carpophores of Tuber aestivum (= uncinatum) (Pacioni 1987;Chevalier and Frochot, 1997;Granetti et al, 2005;Montecchi and Sarasini, 2000;Zambonelli et al 2000;Riousset et al, 2001;García-Montero et al, 2010). However, little is known about the actual capacity of those Pinus species for producing significant amounts of truffles with commercial interest.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it has been observed that Pinus nigra subsp. salzmannii produces carpophores of Tuber aestivum (= uncinatum) (Pacioni 1987;Chevalier and Frochot, 1997;Granetti et al, 2005;Montecchi and Sarasini, 2000;Zambonelli et al 2000;Riousset et al, 2001;García-Montero et al, 2010). However, little is known about the actual capacity of those Pinus species for producing significant amounts of truffles with commercial interest.…”
Section: Discussionmentioning
confidence: 99%
“…Chinese T. aestivum was first reported by Mao [7,8] but without any indication of its location. Moreover, there are no collections deposited in any Chinese herbarium and this taxon was not mentioned in a more recent publication of the same author [9].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, increasing quantities have been exported to the international market, which has *Address correspondence to this author at the DIPROVAL, Facoltà di Agraria, Università di Bologna, Viale Fanin 46, 40127 Bologna, Italy; Tel: +39 0512096579; E-mail: zambonel@agrsci.unibo.it created concern and also interest in the study of these Chinese Tuber species [12]. Chinese truffles have been regularly shipped to Europe, Japan, United States and Australia [7,12,13], due in part to the fact that they are much cheaper than European truffles. T. indicum sensu lato is the predominant Asiatic species exported to the international market and a small quantity of Tuber pseudoexcavatum has been found to be mixed with T. indicum sensu lato in shipments [6,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 60 different kinds of truffles are distributed in the world, most of which grow in Europe, particularly in Italy, France, Spain (Wang & Marcone, 2011). They are known as "diamonds", with a high economic value, which are the most expensive mushrooms in the world (Wang & Marcone, 2011;García-Montero, Díaz, Di Massimo, & García-Abril, 2010).…”
Section: Introductionmentioning
confidence: 99%